Pilot Study of a Brief WeChat Intervention in China to Increase Students' Willingness to Assist a Flushing Student to Reduce Alcohol Use - Fan Zhang; Lok-Wa Yuen; Lanyan Ding; Ian M. Newman; Duane F. Shell (Korean Society for Preventive Medicine, 2018)
Objectives This pilot study tested the effectiveness of a brief alcohol-related intervention delivered by the social media app WeChat to teach about ethanol-induced facial flushing and increase the willingness of students who see another student flushing to suggest that he or she should reduce or stop drinking. In the context of Chinese drinking culture, it is sometimes socially difficult to refuse a drink, even when experiencing physical discomfort, such as flushing. Methods Classrooms of students in a medical university in China were randomly assigned to the intervention or control group. Students in the intervention group were invited to view 3 alcohol education lessons on WeChat during a 2-week period. A pretest and posttest before and after the 2-week period assessed changes in students' willingness to intervene if they saw someone flush while drinking. Data were collected about students' alcohol use and their ratings of the lessons. Results Mixed-design analysis of variance yielded a significant time-by-treatment interaction effect on the variable of willingness to suggest that a flushing person stop or slow down their drinking, and the change was significant between the intervention and control groups. One-way analysis of covariance yielded a significant treatment effect at the posttest, after controlling for the pretest score. Students rated the lessons above the midpoint of the scale for being informative, interesting, and useful. Conclusions The pilot study showed that a brief alcohol-related intervention delivered by WeChat could produce a measurable positive change in the willingness of university students to suggest that a student who flushes should stop drinking. This pilot study also suggested improvements for future lessons and evaluation design.